Synthesis of Vinyl Modified Silica as a High-Performance Liquid Chromatography Stationary Phase - Alzena, Ardine Zada; Rusli, Handajaya; Alni, Anita; Amran, Muhamad Bachri (Jurnal Kartika Kimia, 2025)
Silica can be produced through hydrolysis in alkaline conditions via the Stober process and has two main functional groups, namely siloxane (Si-O-Si) and silanol (Si-OH). Vinyl modified silica can be produced from the hydrolysis of tetraethyl orthosilicate (TEOS) and vinyl trimethoxysilane (VTMS) with 25%(v/v) ammonia. VTMS is used as a silica surface modifying agent. The resulting silica-vinyl modification is then used as a stationary phase to fill a High Performance Liquid Chromatography (HPLC) column. The aim of this research is to synthesize vinyl-modified silica as a HPLC stationary phase and test its performance. Silica-vinyl modification is carried out by first synthesizing silica from TEOS and then modifying the surface using VTMS. Characterization was carried out using a Scanning Electron Microscope (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). SEM characterization gave a spherical shape and a diameter of 1.73-2.02 μm. FTIR identification gave good results with the identification of siloxane signals (Si-O-Si) at 1,097 cm-1 on silica and 2,850 cm-1 and 2,922 cm-1 which were C-H vibrations on silica-vinyl. Qualitative identification carried out by the addition of alkenes with I2 also shows the binding of vinyl groups to the silica surface. The modified silica is then loaded into a 50 mm x 4.6 mm column. The performance test was carried out by separating caffeine and paracetamol compounds. Optimum separation of MeOH:HOH 1:99 eluent with a flow rate of 1 mL/min. The resulting resolution is 1,80 and selectivity is 1.52. The resulting calibration curve has an R2 value of 0.99156 for caffeine and 0.99431 for paracetamol.